A estratégia de atenção nutricional ao pré-natal e puerpério e a integralidade da atenção materno-infantil - Laporte-Pinfildi, Anna Sylvia de Campos [UNIFESP] (2014)
The attention to prenatal care in Brazil historically occupies an important space in the health care of the population. For its effectiveness, are necessary promotion, prevention, diagnosis and treatment. In the city of Santos, SP there was the need to develop strategies to qualify attention to this population. The aim of this study was to identify and evaluate the nutritional care of Prenatal Care and Puerperium held in the city of Santos. Therefore, there were two transversal studies. In Study 1 was made a census of 28 Basic Health Units / Family Health Units (BHU / FHU) of the insular area of Santos to evaluate the structure and process of nutritional care, from the perspective of managers. We interviewed all managers of Primary Care (28) using tool to assess infrastructure, teamwork, the process of work and its place in the nutritional care in prenatal and postpartum care. In Study 2 there was a case study in a BHU in which was implemented in 2010, the Nutrition Care Strategy in Prenatal and Puerperium under the Social Nutrition Stage of the Federal University of São Campus Santos, in order to know the effects of this intervention on the completeness of maternoinfantil care. The universe of this study was composed of 58 women divided into two groups: women who began prenatal care before and after deployment. Evaluated the process of nutritional care compared between the two groups, collecting information of perinatal records and files of children. Statistical analysis was performed using the chi-square test, considering statistically significant p values <0.05. According to the findings of Study 1, nutritionist insertion in the Basic Attention county was the main component of insufficient size structure, a negative effect on nutritional care process, according to an evaluation of 60% of managers. It was found low compliance for the following variables of the process dimension: calculate the Body Mass Index BMI-(35%), monitoring of nutritional status in BMI curve / gestational week (46%) and performance of individual nutritional counseling as routine pre natal (14%). The Study 2 results showed statistically significant improvement in the nutritional care process, with emphasis on: measurement of body height (p = 0.001), pre-pregnancy weight record (p = 0.032), monitoring the BMI chart / gestational week (p = 0.001), newborn weight record at discharge (p = 0.011) and daily weight gain (p = 0.019). It is considered that the Nutrition Care Strategy in Prenatal and Puerperium fostered multidisciplinary attention and contributed to enhance the data records in records. Actions are necessary for their improvement, especially with regard to health care of women in postpartum care and the data records as well as the monitoring of child growth and development using the World Health Organization standards. It is believed that the results obtained in this study can sensitize local managers about the current situation of the municipality maternoinfantil care and subsdiar planning and improvement strategies to consider the nutritional care as essential for comprehensive care.